People with disabilities: An ancient society got it right, but can we? - Razak, Nor Izzati Ab; Hasnan, Nazirah; Putera, Ku Anis Shazura Indera; Gunasagaran, Jayaletchumi; Ahmad, Tunku Sara (De Gruyter, 2018)
Persons with disabilities of today often have difficulty reaching full career and social status, due to physical, functional, practical and psychological factors. The Lenggong Valley, in the state of Perak, Malaysia contains the 11,000 year old remains of a member of the Austramelenesoid family. He was tall, but had several abnormalities. He had a skeletal deformity of the upper limb. His elbow was held flexed, wrist extended and he had an abnormal left middle finger. He also had a scoliosis and a shorter left lower limb. It is estimated that he walked with a limp. However he is estimated to have died at the age of 40 to 45 years, twice the life expectancy of his time. Archeological findings indicated that he was buried as an important person in the tribe, possibly a Shaman. With his abnormalities, he was probably unable to hunt effectively, yet obviously given a more appropriate role to play and able to lead a long life of a respected person, being buried with full honours of his time. An ancient civilization was able to adapt roles so that a person with disabilities could use his unique abilities to contribute to society and lead a respected life, something present society could think about and learn from. If current society could help the disabled to achieve their full potential everyone would stand to benefit.